AlphaBet: Combination of Radium-223 and [177Lu]Lu-PSMA-I&T in men with metastatic castration-resistant prostate cancer (clinical trial protocol) - Kostos, Louise; Buteau, James P.; Yeung, Theresa; Iulio, Juliana Di; Xie, Jing; Cardin, Anthony; Chin, Kwang Y.; Emmerson, Brittany; Owen, Katie L.; Parker, Belinda S.; Fettke, Heidi; Furic, Luc; et al. (Frontiers in Medicine, 2022)
Background: [177Lu]Lu-PSMA is a radioligand therapy used in metastatic castration-resistant prostate cancer (mCRPC). Despite a survival benefit, the responses for many patients receiving [177Lu]Lu-PSMA are not durable, and all patients eventually develop progressive disease. The bone marrow is the most common site of progression. Micrometastases in this area likely receive an inadequate dose of radiation, as the emitted beta-particles from 177Lu travel an average range of 0.7mm in soft tissue, well beyond the diameter of micrometastases. Radium-223 (223Ra) is a calcium-mimetic and alpha-emitting radionuclide approved for use in men with mCRPC with bone metastases. The range of emitted alpha particles in soft tissue is much shorter (≤100 µm) with high linear energy transfer, likely more lethal for osseous micrometastases. We anticipate that combining a bone-specific alpha-emitter with [177Lu]Lu-PSMA will improve eradication of micrometastatic osseous disease, and thereby lead to higher and longer responses. Methods: This is a single-centre, single-arm phase I/II trial evaluating the combination of 223Ra and [177Lu]Lu-PSMA-I&T in men with mCRPC. Thirty-six patients will receive 7.4 GBq of [177Lu]Lu-PSMA-I&T, concurrently with 223Ra in escalating doses (28 kBq/kg – 55kBq/kg), both given intravenously every six weeks for up to six cycles. Eligible patients will have at least two untreated bone metastases visible on bone scintigraphy, and PSMA-positive disease on PSMA PET scan. Patients must have adequate bone marrow and organ function and be willing to undergo tumour biopsies. Patients with discordant disease visible on FDG PET scan (defined as FDG positive disease with minimal or no PSMA expression and no uptake on bone scan) will be excluded. Other key exclusion criteria include the presence of diffuse marrow disease, prior treatment with 223Ra or [177Lu]Lu-PSMA, or more than one prior line of chemotherapy for prostate cancer. The co-primary objectives of this study are to determine the maximum tolerated dose of 223Ra when combined with [177Lu]Lu-PSMA-I&T and the 50% PSA response rate. Conclusion: The AlphaBet trial is a phase I/II study combining 223Ra with [177Lu]Lu-PSMA-I&T in patients with mCRPC. We aim to enroll the first patient in Q3 2022, and recruitment is anticipated to continue for 24 months. Study Registration: NCT05383079